National Pension Scheme: A Veracity of India - Sood, Deepak (International Journal of Psychosocial Rehabilitation, 2020)
The impact of national pension funds has been increased day by day in order to promote the social security or pension saving (private) in the economy. Pension funds also helps in improving the growth of the country for the long run.The Main objective of the pension fund is to attain the higher amount of returns and reduce the risk. As pension funds are considered to be a important part of the capital market in various countries hence these capitals market also help in generating the higher returns where as these returns are varying from the country to country. Many country’s has been in there life expectancies but they also reduce the fertility rates. This paper emphasis on the comparison of NPS is with Mutual funds, debt funds and equity funds with the help of Sharpe ratio and conceptualize the facts with findings that there is an impact of risk and return with relationship at different point or stages of occurrence.